ATRX loss promotes immunosuppressive mechanisms in IDH1 mutant glioma. Issue 6 (24th December 2021) - Hu, Chengchen; Wang, Kimberly; Damon, Ceylan; Fu, Yi; Ma, Tengjiao; Kratz, Lisa; Lal, Bachchu; Ying, Mingyao; Xia, Shuli; Cahill, Daniel P; Jackson, Christopher M; Lim, Michael; et al.
Abstract: Background: ATRX inactivation occurs with IDH1 R132H and p53 mutations in over 80% of Grades II/III astrocytomas. It is believed that ATRX loss contributes to oncogenesis by dysregulating epigenetic and telomere mechanisms but effects on anti-glioma immunity have not been explored. This paper examines how ATRX loss contributes to the malignant and immunosuppressive phenotypes of IDH1 R132H /p53mut glioma cells and xenografts. Methods: Isogenic astrocytoma cells (+/−IDH1 R132H /+/−ATRXloss ) were established in p53mut astrocytoma cell lines using lentivirus encoding doxycycline-inducible IDH1 R132H, ATRX shRNA, or Lenti-CRISPR/Cas9 ATRX. Effects of IDH1 R132H +/−ATRXloss on cell migration, growth, DNA repair, and tumorigenicity were evaluated by clonal growth, transwell and scratch assays, MTT, immunofluorence and immunoblotting assays, and xenograft growth. Effects on the expression and function of modulators of the immune microenvironment were quantified by qRT-PCR, immunoblot, T-cell function, macrophage polarization, and flow cytometry assays. Pharmacologic inhibitors were used to examine epigenetic drivers of the immunosuppressive transcriptome of IDH1 R132H /p53mut /ATRXloss cells. Results: Adding ATRX loss to the IDH1 R132H /p53mut background promoted astrocytoma cell aggressiveness, induced expression of BET proteins BRD3/4 and an immune-suppressive transcriptome consisting of up-regulated immune checkpoints (e.g., PD-L1, PD-L2) and altered cytokine/chemokine profiles (e.g., IL33, CXCL8, CSF2, IL6, CXCL9). ATRX loss enhanced the capacity of IDH1 R132H /p53mut cells to induce T-cell apoptosis, tumorigenic/anti-inflammatory macrophage polarization and Treg infiltration. The transcriptional and biological immune-suppressive responses to ATRX loss were enhanced by temozolomide and radiation and abrogated by pharmacologic BET inhibition. Conclusions: ATRX loss activates a BRD-dependent immune-suppressive transcriptome and immune escape mechanism in IDH1 R132H /p53mut astrocytoma cells.